MEDIA PEMBELAJARAN DAN SUMBER BELAJAR: PERSPEKTIF AL-QURAN DAN HADITS - Said, Abdurrahman (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2023)
The learning process which is a communication process with a reciprocal direction, actually gets quite high attention in Islamic education, that communication must be adjusted between teachers, sources, media and students. This research tries to examine several groups of verses in the Al-Qur'an and Prophetic Hadith, related to how learning resources and learning media are used in the learning process. To complete this research, we uses several units of analysis in the form of two groups of verses in the Qur'an; namely verses 75-78 of surah Al-An'am, verses 51-66 of surah Al-Anbiya and the Hadith regarding the making of the podium narrated by Al-Bukhari. The content analysis uses some classical literature on Al-Qur'an commentary and Hadith explanations which are corroborated with several contemporary references. The results of the discussion show that the two groups of verses and hadiths provide clues related to the function of learning resources, the values of learning experiences and skills for students that can be easily accessed and are individual in nature. In addition, there are cues related to the function as learning media; the liaison between the teacher and students, the effectiveness of connecting material from learning resources delivered by the teacher to students, and the dissemination of material to each student.